Patients' tolerance of bimanual lid retraction versus a metal speculum for intravitreal injections - Alattas K (Dove Medical Press, 2016)
Khadijah Alattas Department of Ophthalmology, College of Medicine, King Abdulaziz University, Jeddah, Saudi Arabia Objective: To compare patients’ acceptance of and correlate their pain level for bimanual versus metal speculum fixation in intravitreal injections. Design: Prospective analysis. Participants: Seventy-three eyes of 56 patients. Methods: A questionnaire indicating patients’ discomfort and pain grading immediately after intravitreal injections using either bimanual fixation or metal speculum fixation (Barraquer Wire Speculum). Results: Fifty-six patients who underwent intravitreal injections were enrolled in this study for various conditions. Patients’ overall pain and discomfort were as follows, right eye – bimanual was 0.3 on our grading scale with a standard deviation of 0.54, right eye – metal was 1.6 on our grading scale with a standard deviation of 1.5, left eye – bimanual was 0.41 on our grading scale with a standard deviation of 0.87, and left eye – metal was 1.91 on our grading scale with a standard deviation of 1.14 (P=0.003). Conclusion: Patients who underwent bimanual fixation had a much more comfortable experience with less pain in comparison to patients who underwent metal speculum fixation. Keywords: AMD, diabetic retionpathy, Avastin, eye injection